In situ coagulation versus pre-coagulation for gravity-driven membrane bioreactor during decentralized sewage treatment: Permeability stabilization, fouling layer formation and biological activity. (1st December 2017) - Ding, An; Wang, Jinlong; Lin, Dachao; Tang, Xiaobin; Cheng, Xiaoxiang; Li, Guibai; Ren, Nanqi; Liang, Heng
Abstract: Gravity-driven membrane filtration systems are promising for decentralized sewage treatment due to their low energy consumption and low maintenance. However, the low stable permeability/flux is currently limiting their wider application. With the ultimate goal of increasing permeability, the aim of this study was to evaluate the effect of coagulation ( in situ coagulation and pre-coagulation) on the performance of a gravity-driven membrane bioreactor (GDMBR) during treatment of synthetic sewage. Results show that in situ coagulation significantly increased permeability (more than two-fold); however, no stabilization of permeability occurred over the whole operation, when non-coagulated and pre-coagulated reactors were compared. The high permeability observed was attributed to the accumulated aluminium floc in the reactor, which prevented formation of fluorescent microbial metabolites (aromatic and tryptophan proteins, as well as fulvic acids), and further avoided membrane pore blocking. In addition, the surface porosity of the fouling layer was improved (from 11.2% to 32.4% for non-coagulated and in situ coagulated reactors). The unstable permeability was possibly associated with lower biological processes within the fouling layer. These might include lower adenosine triphosphate (ATP) content and lower fluorescent metabolites from the extracellular polymeric substances (EPS) caused by the accumulated Al (compared with the control). On the other hand, pre-coagulation improved the level of stable permeability compared with the control (80 versus 40 L/m 2 h bar), mainly because pre-coagulation decreased the EPS content and also maintained high ATP content of the fouling layer. In addition, both coagulation processes reduced the total filtration resistance, mainly the hydraulically reversible resistance and cake layer resistance, which could lower the cleaning frequency. Overall, coagulation could greatly increase the removal efficiency and improve the GDMBR permeability, which would make the process suitable for decentralized wastewater treatment. Graphical abstract: Image 1 Highlights: Applications of in situ and pre-coagulation to GDMBR were evaluated. Permeability was greatly increased by in situ coagulation, but remained unstable. In situ coagulation led to a fouling layer with low ATP and EPS content. Pre-coagulation increased the level of stable permeability compared with control. Pre-coagulation resulted in a fouling layer with high ATP and low EPS content.